Altered expression of TGF alpha and TGF beta 1 in the mucosa of the functioning pelvic ileal pouch. - Campbell, A; Smithson, J; Lewis, C; Kettlewell, MG; Mortensen, N; Jewell, D; McGee, J (1996)
The mucosa of the functioning pelvic ileal pouch undergoes loss of villous height and an increase in crypt cell proliferation as an adaptive response to its new luminal environment. These changes can occur in the absence of inflammation and could be mediated by growth factors such as transforming growth factors alpha and beta 1 (TGF alpha and TGF beta 1). Expression of TGF alpha and TGF beta 1 messenger RNA (mRNA) and protein was determined by in situ hybridization and immunohistochemistry in sections of terminal ileum taken at the time of pouch formation and of subsequent pouch biopsies from 14 patients (total of 90 specimens). Crypt cell proliferation was assessed using the monoclonal antibody MIB-1. As ileal pouch mucosa underwent loss of villous height and crypt hyperplasia, epithelial expression of TGF alpha mRNA and protein decreased. In contrast, TGF beta 1 mRNA and protein were abundant in both normal and flat mucosa. Epithelial expression of TGF beta 1 protein was maximal in flat, inflamed biopsies. These results suggest that although altered expression of TGF alpha and TGF beta 1 mRNA and protein may play some part in the regulation of the adaptive response in ileal pouch mucosa, TGF alpha does not have a direct, positive role in the regulation of crypt cell proliferation.